C5aR antagonist inhibits LPS-induced inflammation in human gingival fibroblasts via NF-κB and MAPK signaling pathways - Chen, Yan (2023)
Objective: Abnormal complement activation is associated with periodontitis. W54011 is a novel non-peptide C5aR antagonist (C5aRA) that exhibits favorable anti-inflammatory effects in various inflammatory models. However, whether W54011 inhibits periodontitis has not yet been fully elucidated. To address this, we have investigated the probable anti-inflammatory mechanism of W54011 in LPS-treated inflammation in human gingival fibroblasts (HGFs). Materials and methods: HGFs were isolated from healthy gingival tissue samples using the tissue block method and were identified with immunofluorescence staining. The CCK8 assay and reverse transcription-PCR (RT-PCR) were used to select the optimal induction conditions for Lipopolysaccharide (LPS) and C5aRA (according to supplementary data S 1 and S 2). The levels of inflammatory cytokines, C5aR, and the activation of NF-κB/MAPK signaling pathways were determined by RT-quantitative PCR (RT-qPCR) and Western blotting. Results: Immunofluorescence results showed that vimentin and FSP-1 were positive in HGFs, and Keratin was negative in HGFs. Immunofluorescence staining demonstrated that C5aRA inhibited LPS-stimulated nuclear translocation of p-p65. RT-qPCR and western blotting showed that C5aRA reduced the expression of IL-1β, IL-6, TNF-α, C5aR, p-p65, p-IκBα, p-JNK, p-c-JUN, and TLR4 in LPS-induced HGFs. Conclusion: In conclusion, these findings suggested that C5aRA attenuated the release of inflammatory cytokines in LPS-induced HGFs by blocking the activation of the NF-κB and MAPK signaling pathways.